[PP.30.02] IMPACT OF STRESS REDUCTION ON BLOOD PRESSURE CONTROL IN PATIENTS TREATED WITH PERINDOPRIL; SHAKE THE HABIT II. (September 2016) - Vasilevski, M.; Hamel, R.; Rampakakis, E.; Sampalis, J.
Abstract : Objective: Stress management has been recognized by the Canadian Hypertension Educational Program (CHEP) as an essential lifestyle modification for hypertension. The study assessed the effectiveness of a patient – centric stress management tool on perceived stress and evaluated the effect of stress reduction on BP control of patients treated with perindopril. Design and method: This was an open label, prospective, randomized phase-IV study. Patients for whom the treating physician had prescribed perindopril independently of the study were enrolled from 74 community physicians across Canada and were randomized to a stress education group (SE) or a control group (CTRL). All patients received motivational letters encouraging them to adhere to the CHEP recommendations. The SE group also received educational material regarding the impact of stress on BP and suggestions on stress management with a CD of autogenic and progressive muscle stress reduction exercises. Main outcome measures were BP and Cohen's Perceived Stress Scale (PSS). Follow up was at weeks 4 and 16 after baseline. Results: A total of 5963 (CTRL: 2, 966; SE: 2, 997) completed the study. Mean (SD) age was 62 (13) years, 47% were female and 75% were Caucasian. Baseline mean (SD) SBP/DBP was 151 (9.75)/89 (8.61) mmHg. Demographics and baseline BP were similar for the two patient groups. The proportion of patients treated with perindopril 4 and 8 mg/day respectively was 61% and 16% at baseline and 38% and 37% at 16 weeks. By 16 weeks significant (P < 0.001) mean (SD) reductions in SBP/DBP of -20(13)/-10(9) mmHg were observed and 64% had achieved target BP. There was no between group difference with respect to change in BP, target BP and PSS at 16 weeks. After adjusting for relevant covariates improved stress management was associated with a significant reduction in SBP (-1.8 mmHg, P = 0.002) and DBP (-0.5, P = 0.213) and increased odds of target BP (OR = 1.4; P = 0.006). Conclusions: Perindopril was effective in reducing BP after 16 weeks of treatment. Improved stress management is associated with better BP control, Identification of effective stress management interventions must be a priority in BP management.